Factores socioeconòmicos y su influencia en la desnutriciòn aguda en niños de 2 - 3 años, atendidos en el centro de salud “Enrique Ponce Luque” Babahoyo - Los Rios, primer semestre del 2018 - Castro Troncoso, Nancy Stefany (2018)
As the slope of malnutrition is the pathological condition derived from the underutilization of essential nutrients in the cells of the body. Malnutrition can be classified as primary when natural nutrients can be contributed by economic, educational and educational, secondary and secondary factors. The absorption or use of food is not adequate. Our main objective is to analyze the influence of socioeconomic factors on acute malnutrition in children aged 2 to 3 years, attended at the Health Center "Enrique Ponce Luque" Babahoyo - Los Ríos, first semester of 2018, as a method used Hypothetical method - deductive Inductive deductive method Descriptive method, fundamental in the research, the most relevant results were used to be able to respond to our problems, the surveys were applied in the Barrio Lindo health center, the conclusion It is recommended to hold informative workshops on prevention Healthy nutritional habits, according to the different ages of children. Encourage health personnel to be aware of children with acute malnutrition problems.